State-Church Synergies in Colonial Empires: Longitudinal Evidence on Missionary Expansion in Africa - Bastian Becker (African Economic History Network (AEHN), 2021)
Christian missions played an essential role for European colonial empires, often entering territories before European powers officially claimed control. While interactions between governmental and religious actors and their long-term consequences have been subject to earlier studies, little is known about the temporal dynamics of colonization. This paper uses new historical data (1792-1924) to explore the timing of Protestant mission entries on the African continent as well as their geographic distribution. It is found that the establishment of a colonial state through a European power more than tripled the number of missions entering a territory. This effect is largely limited to missions from the colonizer's metropole. These national missions also became more likely to set up stations in more advantageous locations than their foreign counterparts. The findings attest to State-Church synergies in colonies and demonstrate the importance of national networks. These findings improve our understanding of how colonial empires expanded and have important implications for the study of colonial and missionary legacies of contemporary outcomes. Future research avenues are discussed.
Keywords: 330